2017
DOI: 10.1161/jaha.117.006508
|View full text |Cite
|
Sign up to set email alerts
|

Precatheterization Use of P2Y 12 Inhibitors in Non‐ST‐Elevation Myocardial Infarction Patients Undergoing Early Cardiac Catheterization and In‐Hospital Coronary Artery Bypass Grafting: Insights From the National Cardiovascular Data Registry ®

Abstract: BackgroundCurrent guidelines recommend early P2Y12 inhibitor administration in non‐ST‐elevation myocardial infarction, but it is unclear if precatheterization use is associated with longer delays to coronary artery bypass grafting (CABG) or higher risk of post‐CABG bleeding and transfusion. This study examines the patterns and outcomes of precatheterization P2Y12 inhibitor use in non‐ST‐elevation myocardial infarction patients who undergo CABG.Methods and ResultsRetrospective analysis was done of 20 304 non‐ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Due to increased platelet action, it is a common practice advocated by guidelines [ 18 ] to pretreat MI patients with antiplatelet adenosine diphosphate P2Y12 receptor antagonist (clopidogrel, prasugrel or ticagrelor) before coronary angiography. However, in recent findings, the increased re-sternotomy and bleeding rates [ 19 ] in MI patients undergoing CABG and non-effectiveness of pre-treatment prior to PCI [ 20 ], question the benefits of routine P2Y12 inhibitor preloading in NSTEMI patients, especially if left main or multivessel disease is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Due to increased platelet action, it is a common practice advocated by guidelines [ 18 ] to pretreat MI patients with antiplatelet adenosine diphosphate P2Y12 receptor antagonist (clopidogrel, prasugrel or ticagrelor) before coronary angiography. However, in recent findings, the increased re-sternotomy and bleeding rates [ 19 ] in MI patients undergoing CABG and non-effectiveness of pre-treatment prior to PCI [ 20 ], question the benefits of routine P2Y12 inhibitor preloading in NSTEMI patients, especially if left main or multivessel disease is suspected.…”
Section: Discussionmentioning
confidence: 99%
“… 30 In upstream-loaded patients, the interval from DA to surgery was only 3–4 days. Contemporary data from the National Cardiovascular Data Registry indicate that the median time from DA to CABG among patients with NSTEMI who are not treated with upstream P2Y 12 i is 43.5 hours, 31 and so the incremental difference may not be as striking as it first appears, particularly since in PLATO, guidance for CABG in ticagrelor-loaded patients was to wait only 24–72 hours. 2 …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the ACCOAST trial demonstrated no interaction between access site and the observed increase in bleeding risk. 28 Nevertheless, decisions regarding access site may not be known at the time of pretreatment; multiple recent observational studies have demonstrated pretreatment is associated with increased bleeding risk among patients who require bypass surgery or among those with an alternate diagnosis (eg, aortic dissection) [29][30][31] ; and most importantly, no benefit in regards to ischemic end points was observed.…”
Section: Jama Network Open | Cardiologymentioning
confidence: 99%